Efektifitas Transmisi Kebijakan Moneter Indonesia Jalur Nilai Tukar Pada Masa Pandemi Covid-19 - Esti Pasaribu; Ratu Eva Febriani; Septriani Septriani (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2021)
This study aims to examine the effectiveness of the exchange rate channel in transmitting monetary policy in Indonesia for the 2002-2020 period. The ultimate target of monetary policy in Indonesia as a measure of the effectiveness of the transmission mechanism in this research is inflation. The data used in this research is secondary data and the form of data is monthly data. The time series data include inflation rates, rupiah exchange rates, SBI interest rates, international interest rates, net imports, and net foreign assets. The analytical tool used in this study is Error Corection Model (ECM) by looking at how the real sector respons to policies issued by the government both in the short and long term. The result is that the exchange rate channel monetary policy has a sovereign affects inflation within two months.